ANALISIS FINANSIAL SISTEM PENGELOLAAN SAMPAH DI WILAYAH KECAMATAN MENGWI KABUPATEN BADUNG - Yansen, I Wayan; Arnatha, I Made (Jurnal Ilmiah Teknik Sipil, 2012)
Abstract :  This paper refers to a previous study conducted in 2004. The previous study analysed the investment value of waste management. The survey was conducted in Mengwi District in Badung Regency. Secondary data were obtained from Badung Cleaning and Landscape and Office while primary data were collected by distributing questionnaire to the local residents. The study showed that Total Construction Costs are Rp. 12,863,050,000.00 with a ratio of 30% private owned capital. The expected Return on Investment or equity rate is 14% and loan capital of 70% used loan interest rate of 6%. The investment analysis produced a positive Net Present Value and the Internal Rate of Return of 26.87%.
Keywords: Analis finansial, sistem pengelolaan sampah